2018 IEEE International Symposium on Information Theory (ISIT) 2018
DOI: 10.1109/isit.2018.8437799
|View full text |Cite
|
Sign up to set email alerts
|

Sufficient Conditions for the Tightness of Shannon's Capacity Bounds for Two-Way Channels

Abstract: New sufficient conditions for determining in closed form the capacity region of point-to-point memoryless two-way channels (TWCs) are derived. The proposed conditions not only relax Shannon's condition which can identify only TWCs with a certain symmetry property but also generalize other existing results. Examples are given to demonstrate the advantages of the proposed conditions. Index Terms-Network information theory, two-way channels, capacity region, inner and outer bounds, channel symmetry. † The authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 9 publications
0
15
0
2
Order By: Relevance
“…Viewing the generalized DM-PTT-TWC as two sets of one-way channels, we further observed that one-way channel components with (relatively) low capacity should be abandoned for efficient transmissions. Future research directions include finding a more general tightness condition for DM-TWCs, identifying the connections between different channel symmetry properties (in particular between the channel symmetry property introduced in this paper and the ones in [10] and [12]), and investigating the transmission of correlated sources over the generalized DM-PTT-TWCs.…”
Section: Examples and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Viewing the generalized DM-PTT-TWC as two sets of one-way channels, we further observed that one-way channel components with (relatively) low capacity should be abandoned for efficient transmissions. Future research directions include finding a more general tightness condition for DM-TWCs, identifying the connections between different channel symmetry properties (in particular between the channel symmetry property introduced in this paper and the ones in [10] and [12]), and investigating the transmission of correlated sources over the generalized DM-PTT-TWCs.…”
Section: Examples and Discussionmentioning
confidence: 99%
“…We also illustrate the possible different shapes of the capacity region and discuss efficient transmission strategies via examples. It is worth mentioning that a by-product of our derivation is a new way to show the tightness of Shannon's capacity inner bound [1] which is complementary to prior methods in [7], [10], [12]. In fact, we find that none of these prior results imply that Shannon's inner bound is tight for Shannon's PTT-TWC (and for our general model under the symmetry property).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The non-adaptive DM-TWC is also called the restricted DM-TWC in [19]. Shannon's inner and outer bounds have later been improved by utilizing auxiliary random variables techniques [9], [11], [26], and sufficient conditions under which his bounds coincide have been obtained [23,24]. However, despite much effort, the capacity region of a general DM-TWC under the vanishing-error criterion remains elusive.…”
Section: Introductionmentioning
confidence: 99%